The effect of deferred tax burden, tax planning and deferred tax assets on profit management (Empirical Study On Manufacturing Companies In The Consumer Goods Industry Sector Listed On The Indonesia Stock Exchange In 2015-2019) - Moch. Febri Sayidil Umam; Sri Aniri; Yogi Ginanjar; Benny Prawiranegara (Finance and Business Management Journal, 2023)
The development of companies in Indonesia is now starting to increase and develop. Managers present financial statements containing information about profits that will be used by internal and external parties in making decisions. These internal and external parties include investors, creditors, government, management itself, and other interested parties. Management performance can be judged from these profit figures. Situation This is what usually encourages managers to carry out deviant behavior in presenting and reporting profit information known as profit management. The research method used is quantitative research using descriptive analysis and verification analysis. The object of this research is a manufacturing company in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2015-2019. Determination of samples in this study using techniques of Purposive Sampling. So that the total number of samples in this study is 90 sample data. The test results state that deferred tax expense and tax planning no significant effect on profit management. While, deferred tax assets have a significant effect on profit management in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2015-2019.